Thermal analysis of Stirling thermocompressor and its prospect to drive refrigerator by using natural working fluid. (1st December 2018) - Wang, Jue; Pan, Changzhao; Luo, Kaiqi; Chen, Liubiao; Wang, Junjie; Zhou, Yuan
Highlights: A novel Stirling thermocompressor (STCP) is proposed. A progressive three order non-equilibrium thermal model of STCP is established. The performances of STCP in no-load and RC-load operation are studied. Helium, nitrogen and hydrogen are compared as the working fluids of STCP. Abstract: The Stirling thermocompressor (STCP), usually working at low frequency (<5 Hz), is a novel Stirling-type external-combustion machine. It utilizes the temperature difference between the heating temperature and ambient temperature to generate the thermoacoustic power and pressure wave for refrigerators. In order to explore the characteristics of STCP, a detailed thermal analysis based on the third order 1-D finite volume model considering the real gas effect and variable physical properties was proceeded. Three natural fluids, helium, nitrogen and hydrogen are chosen as the working fluids and compared with each other. The parameter effects of pressure fluctuation under no-load operation were studied. To understand the output capacities for refrigerator with using different working fluids, the RC load method is adopt to analysis the STCP's capacity and efficiency of the conversion from heat energy to acoustic energy, also the loss characteristics under different working gas. When the working pressure, frequency and heating temperature are 4 MPa, 4 Hz and 800 K respectively, the STCP using helium as the working fluid could output about 380 W acoustic power for the RC load and relative Carnot efficiency is about 33%.